Requirements for technical and financial assistance to improve regional competitiveness: small business sector proposals - Nemdhari, Vic (CCS GeorgetownGY, 1993)
Recognizes that a strong export competitiveness is a pre-requisite for healthy economic development. States that changing market conditions new dictate that our production must become more competitive if our region's business sector is to thrive, progress and develop. Identifies the requirements for financial assistance as mobilizing financing on appropirate terms, proper financial management; and favourable lending criteria. Highlights the requirements for technical assistance as upgrading business management skills; training and counselling programmes; research and information; and industrial estates.